Using an Autograft from the Fibula Diaphysis in the Surgical Treatment of Patients with Fractures of the Proximal Humerus on the Background of Critical Osteoporosis - V. V. Monastyrev; N. S. Ponomarenko; N. V. Tishkov (Acta Biomedica Scientifica, 2021)
The frequency of unsatisfactory results of surgical treatment of patients with a fracture of the proximal humerus remains high and is up to 40 %. This is primarily due to the early instability of the metal structure against the background of osteoporosis and as a consequence of non-fusion of the fracture and the formation  of a false joint. The aim of the study was to evaluate the effectiveness and safety of a new surgical method for treating patients with a fracture of the proximal humerus against the background of critical osteoporosis. After the approval of the local ethics Committee, 2 groups of 10 patients were formed in the clinic: the patients of  main group were operated by the proposed method; the group of clinical comparison was operated by the standard method. In all clinical cases, fractures of the proximal humerus were consolidated on control radiographs. VAS assessment the pain syndrome in the early postoperative period showed that there were no  statistically significant differences in the shoulder joint area in the groups. Three months after surgery, when assessing the volume of movement in the shoulder joint (without the participation of the scapula), there was a statistically significant improvement in the main group: abduction – by 35° and external  rotation – by 25° (p<0.05). When assessing the range of motion of the operated shoulder joint using the ASES scale, a  statistically significant improvement was observed in the main group by 11.6 points after 3 months after  surgery. According to the assessment of the patient›s functional recovery according to the DASH scale, the indicators in the main group were statistically significantly better, which indicates a complete recovery of the shoulder joint function. Thus, the use of the proposed new method, in comparison with other known technologies for surgical treatment of fractures of the proximal humerus, allows achieving a more rigid and stable fixation of bone fragments in the aftermath of trauma and the presence of regional osteoporosis.